CHILDFREE TREND ON SOCIAL MEDIA (CRITICAL ANALYSES STUDIES IN ISLAMIC PERSPECTIVE ) - Maftukhah, Nuriatul; Hilmi, Mustafiqul; Hasaniyah, Nur (Universitas Nurul Jadid, 2023)
The term childfree has captured the public's attention, because it’s embraced by Indonesian influencers who are known through their social media platforms. In Islam, one of the aims of marriage is to multiply society or hifdzu an-nasl, because the Prophet Muhammad ‘Alaihissalam liked his communitiy in large numbers. How ever, the development of cultural pluralizm, some individuals who want to marry tend to avoid having a children for reasons that refer to worldliness prosperity. The purpose of this study is to find out the background of influencers adhering childfree and then connect to the laws of the Qur'an and hadith. This research is qualitative research with descriptive analysis method. Data sources are secondary data, wich is social media accounts of influencers adhering childfree and texts of the Qur'an and hadith. Data are obtained using the listen and record technique and then analyzed descriptively. The result of this study, background childfree adherents is having freedom and independence due to western culture. There are three laws wich explain about childfree. It’s Allowed if reasonable for health and religious reasons. Makruh, if the reason is hassles or worldly prosperity. Haram, if afraid of children only makes them poor.